The critical factors of IT governance and its impact on organizational performance in Malaysian manufacturing industry - Abdollahbeigi, Bentolhoda; Salehi, Farhang (Serbian Journal of Management, 2020)
The purpose of this study is to examine the extent to which senior management’s involvement and demographics of organizational affect the effectiveness of IT governance with the performance of organizations. This is a combination of exploratory and descriptive research that aims to investigate the determinants of IT governance and its effects on organizational performance in Malaysian manufacturing companies. The sample size of 357 collected for this research. Structural equation modeling (SEM) was utilized in this research to investigate the measurement and structural model simultaneously. The findings demonstrated the relationships between the senior management’s involvement and organizational demographics, effective its governance and organizational performance in manufacturing companies in Malaysia. This research is the construction of a theoretically based model which assimilates the senior management’s involvement and organizational demographics, effective IT governance, and performance of organizations. Likewise, discover the most crucial elements that affect effective IT governance to improve the manufacturing company’s performance.